The comfort of strangers - McEwan, Ian 1948- (Vintage Internat., 1994)
"As their holiday unfolds, Colin and Maria are locked into their own intimacy. They groom themselves meticulously, as though someone is waiting for them who cares deeply about how they appear. When they meet a man with a disturbing story to tell, they become drawn into a fantasy of violence and obsession." http://www.loc.gov/catdir/description/random047/94012319.html.